Subdued potential growth: Sources and remedies - Sinem Kilic Celik; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
Global potential output growth has been flagging. At 2.5 percent in 2013-17, post-crisis potential growth is 0.5 percentage point below its longer-term average and 0.9 percentage point below its average a decade ago. Compared with a decade ago, potential growth has declined 0.8 percentage point in advanced economies and 1.1 percentage point in emerging market and developing economies. The slowdown mainly reflected weaker capital accumulation but is also evidence of decelerating productivity growth and demographic trends that dampen labor supply growth. Unless countered, these forces are expected to continue and to depress global potential growth further by 0.2 percentage point over the next decade. A menu of policy options is available to help reverse this trend, including comprehensive policy initiatives to lift physical and human capital and to encourage labor force participation by women and older workers.
Keywords: O40; O47; E20; 330; Potential growth; potential output; advanced economies; emerging market and developing economies